Computer aided design & simulation of a 2.4GHz front-end using EEsof - Lee, Ngai Meng. (2008)
A presentation of laboratory practical CAD experiences in the design and simulation of both active and passive microwave circuits are given. The CAD exercises are carried out using the HP 9000 series 425 workstation and the EEsof Communications Design Suite Version 6.0 from Hewlett Packard.